Investigating the factors influencing the adoption of m-banking: a cross cultural study. Issue 4 (1st June 2015) - Mortimer, Gary; Neale, Larry; Hasan, Syed Fazal E; Dunphy, Benjamin
Abstract : Purpose: – Little is known about the adoption of mobile banking technologies in emerging Asian economies. The purpose of this paper is to empirically examine the motivators that influence a consumer's intentions to use mobile banking. Design/methodology/approach: – A web-based survey was employed to collect data from 348 respondents, split across Thailand and Australia. Data were analysed by employing exploratory and confirmatory factor analyses, path and invariance analyses. Findings: – The findings indicate that for Australian consumers, perceived ease of use, perceived usefulness (PU) and perceived risk (PR) were the primary determinants of mobile banking adoption. For Thai consumers, the main factors were PU, PR and social influence. National culture was found to impact key antecedents that lead to adoption of m-banking. Research limitations/implications: – The actual variance explained by the study's model was higher in Australia (59.3 per cent) than for Thailand (23.8 per cent), suggesting future research of m-banking adoption in emerging Asian cultures. Practical implications: – The authors identify the important factors consumers consider when adopting m-banking. The findings of this research give banking organisations a foundational model that can be used to support m-banking implementation. Originality/value: – The study is perhaps the first to examine and compare the intention to adopt m-banking across Thai and Australian consumers, and responds to calls for additional research that generalises m-banking and m-services acceptance across cultures. This study has proposed and validated additional constructs that are not present in the original SST Intention to Use model.